Endoscopic tympanoplasty vs microscopic tympanoplasty in tubotympanic csom: a comparative study of 44 cases - Patel, Jaimin; Aiyer, Ranjan G.; Gajjar, Yogesh; Gupta, Rahul; Raval, Jayman; Suthar, Pokhraj P. (International Journal of Research in Medical Sciences, 2017)
Background: Tympanoplasty is one of the commonest operations performed on the middle ear. Endoscopes are increasingly used for various middle ear surgeries. The objective was to determine merits and demerits of the endoscope as compared to the microscope in myringoplasty surgery and to compare the results of both group. Methods: Between the time period of January 2014 to September 2014, 44 patients underwent myringoplasty, 22 were endoscope assisted and 22 were microscope assisted. Results of surgery were compared at the end of 3 months post surgery. Results: In both groups, equal number of patients i.e. 15 (68.18%) had a successful outcome. Conclusion:Panoramic, wide angle, and magnified view provided by endoscope as well as ability to easily negotiate through EAC and provide uninterrupted image overcomes most of the disadvantage of microscope. In our study success rate was equal between endoscopic and microscopic technique. In terms of morbidity and postoperative recovery endoscope produced better results. Loss of depth perception and one handed technique are some of the disadvantage of endoscope that can be overcome with practice. Thus, Endoscopic tympanoplasty can be a good alternative of microscopic tympanoplasty.